Production of spray-dried enzyme-modified cheese powder a plant design - Chua, Timothy Moses; Reglos, Angelie Joice; Yap, Joseph II
Enzyme-modified cheese powder can be applied in cheese-flavored snacks. In the Philippines where the demand for cheese-flavored snacks in high and yet the supply is imported, the need to product local cheese power is imminent. EMC can supply the need while using less of milk. The plant is designed to compete with the global cheese powder industry. A few local sources of milk is present in the Philippines. The location of the proposed plant is based upon these sources, and it was decided that the plant be placed in Laguna The conversion of raw materials into the desired enzyme-modified cheese product through the developed herein is largely based on traditional methods of cheese manufacture. Milk is pasteurized, and then separated into curds and whey. The only difference is the addition of one step where curds are aged with enzymes and then dried to produce the final product. Some risks are involved in the production plant. Since the plant manufactures food, less risk is involved, and the largest risk are inhalation of small particles such as enzymes and EMC powder. Employees are to observe proper PPE and safety precautions to protect themselves during the process. The proposed plant is designed coming from milk as the raw material to a packaged cheese powder as the product ready for selling. Mass and energy balances signify that the plant is indeed working with all mass and energy accounted for. Process control and instrumentation diagrams used to ensure that the processes are as least erroneous as possible. The waste production includes whey, hot air, exhaust gases and waste water. Whey is discarded to local pig farmers while hot air and exhaust are discarded in the surroundings. The plant uses natural gas for combustion fuel in the furnace, air for combustion and heating fluid for plant heat exchangers and spray dryers, electricity for curdling vessels and enzyme reactors and water for cleaning. Several equipment proposed to be used for the plant has been designed. These have been chosen amidst comparison with other equipment with nearing functions. HAZOP studies have been analyzed per equipment, along with its process control scheme and specifications. The overall profitability of the plant is analyzed by determining the total investment, payback period, Internal Rate of Return and Net Present Value. Also, the paybacks sensitivity and plants breakeven data are considered. The plant is profitable with a total capital investment of Php 925,957,043.77 and payback of 10.15 years with 6 percent Internal Rate of Return (IRR). It also has a Net Positive Value of Php 19,534,233.19 using 6.2 percent discount factor. In addition, the payback is most and least sensitive to the total product sales and capital investment respectively. The breakeven and shutdown points occur at 2.5 percent and 1 percent capacity respectively. These values are much smaller, which shows the plants earning capacity above 2.5 percent.